Beating the grog: An evaluation of the Tennant Creek liquor licensing restrictions - Gray, Dennis; Saggers, S.; Atkinson, D.; Sputore, Brooke; Bourbon, D. (2000)
A study was conducted to review the effectiveness of, and community attitudes towards, increased restrictions on the availability of alcohol in Tennant Creek, Australia. Estimates of quarterly per capita consumption of pure alcohol by persons 15 years and over, admissions data from the local hospital, women's refuge and sobering up shelter, and police data on detentions in custody and common offences were compared for the 12 months prior and 24 months subsequent to the introduction of the restrictions. A random sample survey of residents aged 18 and over was conducted to ascertain attitudes towards the restrictions. Results showed that over the two years following the introduction of the restrictions, there was a reduction of 19.4% in annual per capita consumption of pure alcohol. This was accompanied by declines in: hospital admissions for acute alcohol-related diagnostic related groups; and persons taken into police custody and the proportions of offences reported on Thursdays. A majority of survey respondents was in favour of retaining or strengthening the existing restrictions. It is concluded that the restrictions were effective in reducing alcohol consumption and acute related harm and had the support of the majority of people in Tennant Creek. On the basis of this evidence, the NT Liquor Commission made a decision to retain them. Restrictions do not provide a simple answer to the problems associated with excessive alcohol consumption. However, they can be an effective part of a broad public health strategy to deal with such problems.